Pengaruh Sektor Pariwisata Terhadap Penyerapan Tenaga Kerja Di Kabupaten/Kota Daerah Istimewa Yogyakarta Tahun 2007-2019 - Ninda Ayuk Aktaniensia; Jurni Hayati (Tirtayasa Ekonomika, 2023)
The number of workforce in the Special Region of Yogyakarta in recent years has continued to increase, this increase is not followed by the availability of sufficient job opportunities so that this causes unemployment. The tourism sector has an important role in job creation. The employment in the tourism sector in the Regency/City of the Special Region of Yogyakarta has fluctuated and uneven in recent years, so it is necessary to develop the tourism sector in the Regency/City of the Special Region of Yogyakarta in order to create more jobs. The purpose of this study is to analyze the effect of the number of tourist objects, travel agencies, tourists on the employment in the tourism sector in the Regency/City of the Special Region of Yogyakarta in 2007-2019. The method used in this study is the panel data regression method and the data used are secondary data obtained from the Central Statistics Agency (BPS), the Tourism Office, the Manpower and Transmigration Office of the Special Region of Yogyakarta. In this study, it was found that the number of tourist objects had a positive and insignificant effect on the employment variable. The number of travel agents has a positive and significant effect on the variable of employment. The number of tourists has a negative and significant effect on the employment variable.